2014
DOI: 10.1186/1477-7827-12-79
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in estrogen receptors predict the risk of male infertility: a meta-analysis

Abstract: BackgroundEstrogen receptors play an important role in mediating estrogen action on target tissues, and the estrogen is relevant to male infertility. Single nucleotide polymorphisms (SNPs) in estrogen receptors may be associated with the risk of male infertility. A variety of case control studies have been published evaluating this association. However, the accumulated studies have shown inconsistent conclusions.MethodsTo further determine the potential association between the four common SNPs (rs2234693, rs93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…Approximately 50 % of infertility cases are attributed to male factors (Zorrilla and Yatsenko, 2013[ 67 ]). It is widely believed that several genetic factors may result in spermatogenesis failure and sperm impairment, including single gene mutations and chromosomal abnormalities (Li et al, 2014[ 31 ]). Androgens are essential hormones for male sex differentiation, normal development, spermatogenesis, and sexual behavior (Nilsson et al, 2015[ 43 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50 % of infertility cases are attributed to male factors (Zorrilla and Yatsenko, 2013[ 67 ]). It is widely believed that several genetic factors may result in spermatogenesis failure and sperm impairment, including single gene mutations and chromosomal abnormalities (Li et al, 2014[ 31 ]). Androgens are essential hormones for male sex differentiation, normal development, spermatogenesis, and sexual behavior (Nilsson et al, 2015[ 43 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The post-hatching increase of the ERα expression in the gonads can be justified to support the increased activity of the estrogen in gonads for the reproductive development in male chicken with age, as per the latest finding of the role of estrogen in the male reproductive system observed in many species [4,18,19]. The studies involved in male infertility and ER knocked down mice models revealed that estrogen activity which is crucial in spermatogenesis and seminal fluid secretion is mediated by the ERα and hence holds utmost importance in the mammalian male testes [19,20]. A similar role of ERα expression could be suggested for avian model too with the results of the current study.…”
Section: Resultsmentioning
confidence: 94%
“…Although the functional implications of the SNPs rs2234693, rs4986938, and rs1256049 have not been fully determined, we hypothesized that these intronic variants could modify the binding of BPA to ERs altering its metabolism and subsequent excretion, since some previous studies reported an association with different conditions [ 44 46 ] suggesting that these SNPs have an important biological role. Studies of genetic differences in substances metabolic pathways that can affect individual responses are in early stages and should be performed in many areas of dental research in order to establish a future field of personalized dentistry.…”
Section: Discussionmentioning
confidence: 99%